2019
DOI: 10.1038/s41598-019-55747-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein components of ribonucleoprotein granules from Drosophila germ cells oligomerize and show distinct spatial organization during germline development

Abstract: The assembly of large RNA-protein granules occurs in germ cells of many animals and these germ granules have provided a paradigm to study structure-functional aspects of similar structures in different cells. Germ granules in Drosophila oocyte’s posterior pole (polar granules) are composed of RNA, in the form of homotypic clusters, and proteins required for germline development. In the granules, Piwi protein Aubergine binds to a scaffold protein Tudor, which contains 11 Tudor domains. Using a super-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 45 publications
(62 reference statements)
2
39
0
Order By: Relevance
“…Glial granules, described in this work, show distinct clusters of their protein components whose roles were mainly restricted to the development of germ cells where they assemble in membraneless RNA-protein granules (germ granules). Recently, it was shown that germ granules in Drosophila germ plasm are assembled from distinct partially overlapping protein and RNA homotypic clusters 5,7,8 . Similar to germ granules, glial granules show distinct protein clusters, which partially overlap, suggesting that the mechanisms of the assembly of glial granules is similar to germ granules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glial granules, described in this work, show distinct clusters of their protein components whose roles were mainly restricted to the development of germ cells where they assemble in membraneless RNA-protein granules (germ granules). Recently, it was shown that germ granules in Drosophila germ plasm are assembled from distinct partially overlapping protein and RNA homotypic clusters 5,7,8 . Similar to germ granules, glial granules show distinct protein clusters, which partially overlap, suggesting that the mechanisms of the assembly of glial granules is similar to germ granules.…”
Section: Discussionmentioning
confidence: 99%
“…ermline (germ) cells give rise to every cell type in the nextgeneration organism after the union of the egg and sperm 1,2 , and they express specific proteins and RNA that are assembled into large and dynamic membraneless granules referred to as germ granules [3][4][5][6][7][8][9] . Components of germ granules are required for germline fate 1,9,10 .…”
mentioning
confidence: 99%
“…Polar granule targeting and assembly into homotypic clusters appears to involve different 3′ UTR elements, at least for pgc RNA (Eagle, Yeboah‐Kordieh, Niepielko, & Gavis, 2018). A more recent study indicates that two polar granule proteins, Aub and Tud, also form distinct clusters within the granules (Vo et al, 2019).…”
Section: Polar Granule Formation Involves Specific Molecular Associations and Nonspecific Physical Processesmentioning
confidence: 99%
“…Somatic development in the absence of Tud still takes place, but germ granule mRNPs do not assemble, and PGCs are not induced ( 31 ). Among TDRDs, Tud has the largest number of eTUD domains that interact with sDMAs of Aub ( 33 , 49 ). Along with Aub–piRNA binding of mRNAs ( 35 ), these multivalent interactions are critical for germ granule mRNP assembly.…”
Section: Discussionmentioning
confidence: 99%